Protective efficacy of a polyvalent influenza A DNA vaccine against both homologous (H1N1pdm09) and heterologous (H5N1) challenge in the ferret model. Issue 34 (9th August 2021) - Guilfoyle, Kate; Major, Diane; Skeldon, Sarah; James, Heather; Tingstedt, Jeanette L.; Polacek, Charlotta; Lassauniére, Ria; Engelhardt, Othmar G.; Fomsgaard, Anders
Abstract: This study describes the protective efficacy of a novel influenza plasmid DNA vaccine in the ferret challenge model. The rationally designed polyvalent influenza DNA vaccine encodes haemagglutinin and neuraminidase proteins derived from less glycosylated pandemic H1N1 (2009) and H3N2 (1968) virus strains as well as the nucleoprotein (NP) and matrix proteins (M1 and M2) from a different pandemic H1N1 (1918) strain. Needle-free intradermal immunisation with the influenza DNA vaccine protected ferrets against homologous challenge with an H1N1pdm09 virus strain, demonstrated by restriction of viral replication to the upper respiratory tract and reduced duration of viral shedding post-challenge. Breadth of protection was demonstrated in two heterologous efficacy experiments in which animals immunised with the influenza DNA vaccine were protected against challenge with a highly pathogenic avian influenza H5N1 virus strain with reproducible survival and clinical outcomes.